Voto plural - Peixoto, Julia Santolin (2024)
This work proposes to analyze the Brazilian model of multiple voting shares, established by Law No. 14,195/2021, bringing to light the discussions which gave grounds to the respective legislative process, as well as the international context that led not only Brazil, but several other jurisdictions to authorize the use of such enhancing mechanism in their legislations. The national legislative process was divided into two main groups: one that defended the broadest contractual freedom and the other opposed to the authorization of the enhancing mechanism and that, at the limit, would support its approval provided that it was accompanied by safeguards aiming the protection of the interests of minority shareholders. The result was the creation of a model that combines a system of protective norms for minority shareholders with few spaces left for the private autonomy. Based on an analysis of international models of multiple voting shares, their use and their consequences, this study seeks to show that, in the abstract, there is no ideal governance recipe and that the results generated by leverage structures are diverse and perceived in different ways around the world. The experience of countries in Continental Europe, the birthplace of the multiple voting shares, indicates that concerns related to its misuse arise from agency problems between the controlling shareholder and minority shareholders, which tend to intensify in structures with a greater degree of disproportion between ownership and control. In Anglo-Saxon law systems, which stock markets are mainly dominated by companies with dispersed capital, differently from the Continental European case, agency problems are related to managerial abuses, generating tensions between company managers and their shareholders. The present study demonstrates that agency problems exist regardless of the corporate structure adopted and the degree of concentration of control, changing only the way in which these problems manifest themselves. This indicates that the most efficient way to reach the optimal point of balance between the interests of controllers and minority shareholders may not be the prohibition of a certain governance structure, but rather the facing of the problems generated by each of them, through the creation of a system adapted to the respective economic reality. Solutions to agency problems can be diverse and vary from the voluntary implementation of internal corporate control structures recommended by international codes as best corporate governance practices, to regulatory control and the creation of mandatory rules designed to limit the degree of enhancement and to protect the interests of shareholders that do not benefit from the enhanced structure. In Brazil, regulatory control over multiple voting shares was adopted through the creation of a system of safeguards designed to protect minority shareholders. The conclusions of this work indicate that the combination of safeguards in the Brazilian model may encumber the use of multiple voting shares